Il tema del ritratto in quattro epigrammi dell’Anthologia Latina - PRIVITERA, Tiziana (AL. Rivista di studi di Anthologia Latina, 2013)
Abstract This paper deals with some ekphrastic epigrams of the Latin Anthology, focusing on some rhetorical aspects of their structure; it also discusses some issues of textual criticism.